KNOWLEDGE OF BREAST SELF-EXAMINATION AMONG WOMEN WITH TEENAGE DAUGHTERS - Dewi Andriani; Restuning Widiasih; Citra Windani Mambang S (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Background, the incidence of breast cancer in women increases every year worldwide including Indonesia. Breast Self-Examination (BSE) is an early detection method for detecting breast cancer that can be done by all women. However, research in Indonesia that examines women's knowledge about BSE, especially in women who have teenage daughters is limited. The purpose of this study was to identify women's knowledge about BSE, especially women with teenage daughters. Method, This study was quantitative descriptive research. The samples were selected using the total sampling technique. The number of samples was 138 women who have teenage daughters. This study was conducted in Sarijadi Village, Bandung. The research instrument was a knowledge questionnaire about BSE. Data were analyzed using frequency distribution. The results of the study, women had a moderate level of knowledge about BSE (51.4%) Women's knowledge was good in the component of purposes and benefits of the BSE (79.7%), and they had poor understanding related to identifying sources to conduct BSE to their daughters (73.2%), Conclusions and recommendation, women have good knowledge about the purposes and benefits of BSE, however they had lack of knowledge about the role of women in supporting girls to conduct BSE. Women need information from health workers relates to their roles in conducting BSE to their daughters. Further research is needed to examine the knowledge and role of fathers in women’s health especially daughters including early detection of cancer as supporting and maintaining daughters' health in the family are parents’ responsibilities including father. Keywords: BSE, breast cancer, health knowledge, mothers, teenage women.